On the Fauna of Gasteruptiid Wasps (Hymenoptera, Evanioidea, Gasteruptiidae) of Belarus - Ostrovsky, A. M. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2022)
Based on the samples of gasteruptiid wasps belonging to the family Gasteruptiidae and genus Gasteruption Latreille, 1796 collected in Gomel area during 2005–2021, the six species are recorded for the first time from Belarus. A brief information on distribution and ecology of these species is given.